Energy and Exergy Analysis of Ocean Compressed Air Energy Storage Concepts - Vikram C. Patil; Paul I. Ro (Journal of Engineering)
Optimal utilization of renewable energy resources needs energy storage capability in integration with the electric grid. Ocean compressed air energy storage (OCAES) can provide promising large-scale energy storage. In OCAES, energy is stored in the form of compressed air under the ocean. Underwater energy storage results in a constant-pressure storage system which has potential to show high efficiency compared to constant-volume energy storage. Various OCAES concepts, namely, diabatic, adiabatic, and isothermal OCAES, are possible based on the handling of heat in the system. These OCAES concepts are assessed using energy and exergy analysis in this paper. Roundtrip efficiency of liquid piston based OCAES is also investigated using an experimental liquid piston compressor. Further, the potential of improved efficiency of liquid piston based OCAES with use of various heat transfer enhancement techniques is investigated. Results show that adiabatic OCAES shows improved efficiency over diabatic OCAES by storing thermal exergy in thermal energy storage and isothermal OCAES shows significantly higher efficiency over adiabatic and diabatic OCAES. Liquid piston based OCAES is estimated to show roundtrip efficiency of about 45% and use of heat transfer enhancement in liquid piston has potential to improve roundtrip efficiency of liquid piston based OCAES up to 62%.